LNG boil-off gas reliquefaction by Brayton refrigeration system – Part 1: Exergy analysis and design of the basic configuration. (1st June 2019) - Kochunni, Sarun Kumar; Chowdhury, Kanchan
Abstract: Heat inleak through insulation in the storage tanks produces boil-off gas (BOG) in LNG-carrying ships. Reverse Brayton cycle (RBC) with nitrogen is often chosen as the refrigeration cycle to reliquefy BOG to prevent loss of valuable gas and environmental pollution. In this paper, parametric evaluations of a basic RBC-based reliquefaction system are done based on exergy analysis. The analyses revealed that formation of liquid at turbine exit and close minimum temperature approach/temperature pinch in the BOG condenser plateaus out the improvement of performance of the RBC based reliquefaction system. The specification of equipment and operating parameters are determined to derive the highest savings in terms of power consumption and recovery of BOG. If RBC is operated in the range of 10–50 bara, close to 93% of BOG is reliquefied. Total reliquefaction is possible only if the RBC is designed with compressor suction at 4 bara. However, it increases the sizes of pipelines, compressor and heat exchangers. All parameters are non-dimensionalized to facilitate application of the results to any capacity of LNG-carrying ship. Part 2 of this paper presents the analyses on thermodynamically improved configurations of reliquefaction systems. Highlights: Economics of boil-off gas reliquefaction systems provided with sample calculation. Analysis is based on realistic composition of BOG that includes nitrogen. Liquid formation at turbine exit is not allowed to ensure long-term safe operation. Nondimensionlization of parameters helps to apply results to any size of LNG ship. Definition of rational exergy efficiency accounts for loss of methane through vent.